2021
DOI: 10.3390/nano11112973
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Spatial Charge in Thermally Poled Glasses via Nanoparticles Formation

Abstract: It is shown for the first time that the vacuum poling of soda-lime silicate glass and the subsequent processing of the glass in a melt containing silver ions results in the formation of silver nanoparticles buried in the subanodic region of the glass at a depth of 800–1700 nm. We associate the formation of nanoparticles with the transfer of electrons from negatively charged non-bridging oxygen atoms to silver ions, their reduction as well as their clustering. The nanoparticles do not form in the ion-depleted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…This indicates lack of Ag in coating over both, step and poled region suggesting that Ag has diffused into glass regardless to poling. This is in accordance with another study where is shown that Ag + from hot salt melt bath enter into vacuum poled glass and form NPs there [32]. In our case NPs in glass were not observed after coating removal.…”
Section: Role Of H + /H 3 O +supporting
confidence: 94%
“…This indicates lack of Ag in coating over both, step and poled region suggesting that Ag has diffused into glass regardless to poling. This is in accordance with another study where is shown that Ag + from hot salt melt bath enter into vacuum poled glass and form NPs there [32]. In our case NPs in glass were not observed after coating removal.…”
Section: Role Of H + /H 3 O +supporting
confidence: 94%